The Relation Between the Life Meaningfulness and the Level of Perceived Social Support Among Elderly People Living in Nursing Homes in Isfahan - Atefe Ahmadi; Hossein Abedi Parija; Mojtaba Habibi; Elahe Sadeq; Sorour Sadat Maddahi (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: The present study aimed to examine the life meaningfulness among the elderly people living in nursing homes of Isfahan, Iran based on their perceived social support from 3 sources of family, friends, and significant others. Methods & Materials: In this research, a total of 120 older people (68 men and 52 women) were selected from the nursing homes of Isfahan through convenience sampling method, and their data were analyzed using Zimet et al. perceived social support and the life meaningfulness questionnaires (1988). Results: The results of stepwise and multiple regression analyses showed that 28.2% of individual differences regarding the life meaningfulness in the elderly people were related to the personal differences in their perceived social support (from family, friends, and significant others), in which the family and other significant persons had the most prominent effect on explaining the changes and in predicting the meaningfulness of life among the elderly. This correlation was statistically significant (P=0.001). Based on analysis of variance, the explained regression model is also significant and linear because the value of F test for determining the effect of independent variables on life meaningfulness of the older people equals 15.353, which is significant (P=0.001). The significance of regression coefficients shows that the family significantly predicts the life meaningfulness of the elderly people. This means that 19.8% of variance is common between family and life meaningfulness of older people. This figure increases to 27.1% by adding significant others to the equation. Conclusion: The results showed that the older people who receive stronger social support also have significantly stronger feelings of meaning in their lives. In other words, the feeling of meaning in the life is significantly related to perceived strong social support. In a way, an important part of individual differences in meaningfulness of the older people’s lives is related to their different perceived social support. Therefore, today with regard to social changes and busy life of children and accordingly their low relation with old parents, it is anticipated that the low perceived support from the family of the older people (which is the most important predicting factor of life meaningfulness among other factors of perceived social support) will affect the meaningfulness of their lives. Considering what older people told in their interviews with regard to the role of the family on promoting the quality of life among them and reaching a joyful experience of life meaningfulness, it is expected that by increasing the quality and quantity of relationship of the family members with older people, their needed support could be provided. This activity requires family members to sufficiently know and understand the physical and mental condition of the older people. Considering the effectiveness of perceived social support of older people on their life meaningfulness, this study generally showed that a higher attention to components of perceived social support is felt among this vulnerable group of older people.